Daily timing of low tide drives seasonality in intertidal emersion mortality risk - Buckee, Joanna; Hetzel, Yasha; Edge, William; Verduin, Jennifer; Pattiaratchi, Chari (Frontiers in Marine Science, 2022)
Abstract Sea level exerts a fundamental influence on the intertidal zone, where organisms are subject to immersion and emersion at varying timescales and frequencies. While emersed, intertidal organisms are exposed to atmospheric stressors which show marked diurnal and seasonal variability, therefore the daily and seasonal timing of low water is a key determinant of survival and growth in this zone. Using the example of shallow coral reefs, the coincidence of emersion with selected stressors was investigated for eight locations around the Australian coastline. Hourly water levels (1992 – 2016) from a high-resolution sea level hindcast (http://sealevelx.ems.uwa.edu.au), were linked to maximum surface solar radiation data from the Copernicus ERA5 atmospheric model and minimum atmospheric temperature observations from the Australian Bureau of Meteorology to identify seasonal patterns and historical occurrence of coral emersion mortality risk. Local tidal characteristics were found to dictate the time of day when low water, and therefore emersion mortality risk occurs, varying on a seasonal and regional basis. In general, risk was found to be greatest during the Austral spring when mean sea levels are lowest and a phase change in solar tidal constituents occurs. For all Great Barrier Reef sites, low tide occurs close to midday during winter and midnight in the summer, which may be fundamental factor supporting the historical bio-geographical development of the reef. Interannual variability in emersion mortality risk was mostly driven by non-tidal factors, particularly along the West Coast where El Niño events are associated with lower mean sea levels. This paper highlights the importance of considering emersion history when assessing intertidal environments, including shallow coral reef platform habitats, where critical low water events intrinsically influence coral health and cover. The study addresses a fundamental knowledge gap in both the field of water level science and intertidal biology in relation to the daily timing of low tide, which varies predictably on a seasonal and regional basis.